Social Injustice: The Dilemma of Family Resilience in Early Marriage to Supporting Regenerative Development - Marlina, Siti; Adawiyah, Robi’atul; Maryani, Maryani; Elvira Zahara, Anzu; Guswendra, Rahmat (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2025)
This research aimed to thoroughly explore the problem of social injustice in the context of early marriage. It positioned the subject matter as a significant dilemma that undermines family resilience and hinders the pursuit of equitable regenerative development. Accordingly, the objectives of the investigation include analyzing how social injustice manifests in the practice of early marriage and how this practice serves as an obstacle to equitable regenerative development. In order to achieve the stated objective, the investigation was conducted using a normative approach. The obtained results showed that social injustice, in the context of early marriage, significantly disrupted family resilience, thereby presenting a substantial challenge to the realization of regenerative development. Based on the observations made, early marriage, which was found to be predominantly driven by socio-economic pressures, cultural norms, and lack of education, weakened family resilience. As a result, the respective capabilities of families to contribute to regenerative development were substantially diminished.